A construção do leitor ficcional em The portrait of a lady e The wings of the dove de Henry James - Neves, Larissa Garay (2016)
Henry James was one of the most renowned writers at the turn of the nineteenth into the twentieth century and is still known for his vast number of literary works and studies about the art of fiction. In his prefaces and critical essays, James discussed his own method of writing fiction, with a special focus on point of view and on issues related to the reception of his fictional work. In this sense, James also considered the importance of the role of the reader to the point of claiming in one of his prefaces: ―attentive reading, I avow, is what, at every point just like here, I completely invoke and hope for‖ (JAMES, 2009, p. 15). This dissertation discusses the construction of the fictional reader in two of James novels: The Portrait of a Lady (1886) and The Wings of the Dove (1902). Written twenty years apart from each other, these novels have meaningful similarities in their themes. The aim is to analyze how differences in the manipulation of point of view have implications to the rhetorical configuration of different readers in the two novels. In The Portrait of a Lady, James basically uses one single center of consciousness to narrate the story and constructs a reader that is gradually more participative and critical. In The Wings of the Dove, on the other hand, James opts for a more impersonal mode of presentation of the story, so the narrative is developed through several centers of consciousness. As a consequence, the configured reader is critical and inferential throughout the whole narrative because the gaps intentionally built by the writer have to be constantly filled. In short, our discussion shows that, along his career, Henry James projected readers that should be more and more critical.